Cross-Cultural Localisation of Serbian Tourism Destinations’ Websites: Cases of Websites of Tourism Organisations of the Cities of Belgrade, Novi Sad and Niš - Stojiljković, Aleksandra; Grubor, Aleksandar (Anali Ekonomskog fakulteta u Subotici, 2025)
Tourism and culture are inextricably linked. Visiting another country with a different culture gives tourists the opportunity to gain different perspectives and enjoy the destination as well. As a result of the development of ICT, but also the development of the web as a primary source of information on tourism destinations, international tourism has increased over the past two years. The importance of cross-cultural adaptation of tourism destinations’ websites grows, so the purpose of this study is to examine the state of cross-cultural localisation activities and practices on the websites of tourism organisations in three cities: 1. Tourism organisation of Belgrade, 2. Tourism organisation of the city of Novi Sad, and 3. Tourism organisation of Niš. All three tourism organisations participated in an open-ended survey for this purpose, and the results showed that localisation was recognised as an important component of online marketing communication.